The Scripts of Robert of Torigni: Some Notes of Conjectural History - Thomas N. Bisson (Tabularia)
This article argues that, while in agreement with B. Pohl that certain annotations in manuscripts of mid s. xii can safely be attributed to the hand of Robert of Torigni (RT), other passages (chiefly in Avranches, Bibliothèque patrimoniale, ms 210, fol. 112v-115r, and in ms 211, fol. 76r) cannot safely be attributed to anyone other than RT, or to a scribe working under his close direction. Moreover, certain markings in rubrics and datings of Leiden ms BPL 20 may be in RT’s hand. In addition, I conjecture that the notations .N. and .a. in several manuscripts dating mostly before 1154 were written by RT.